1001 Inventions That Changed the World - Jack Challoner (B.E.S. Publishing; For the Us & Can, 2009)
We take thousands of inventions for granted, using them daily and enjoying their benefits. But how much do we really know about their origins and development? This absorbing new book tells the stories behind the inventions that have changed the world, with details aboutï¿½